POTENTIALS AND CHALLENGES IN ORAL TRADITION RESEARCH AND EDUCATION: SYNCHROTEXT SOFTWARE. - SEITEL, PETER (History in Africa: A Journal of Method, 2010)
The article discusses the use of Synchrotext computer software for representing oral tradition performances. It comments on the usefulness of the software for education, academic collaboration, and preservation. The author examines its use for research and analysis. He also provides instructions for downloading and utilizing Synchrotext software and suggests that Adobe Flash should be the programming platform. The article considers the software's representation of speakers' voice, time, and intonation.